Internalized Functional DNA Aptamers as Alternative Cancer Therapies - Marshall, Morgan L.; Wagstaff, Kylie M. (Frontiers in Pharmacology, 2020)
Despite major advances, cancer remains one of the largest burdens of disease worldwide. One reason behind this is that killing tumour cells without affecting healthy surrounding tissue remains a largely elusive prospect, despite the widespread availability of cytotoxic chemotherapeutic agents. To meet these modern healthcare requirements, it is essential to develop precision therapeutics that minimise off-target side-effects for various cancer types. To this end, highly specific molecular targeting agents against cancer are of great interest. These agents may work by targeting intracellular signalling pathways following receptor binding, or via internalisation and targeting to specific subcellular compartments. DNA aptamers represent a promising molecular tool in this arena that can be used for both specific cell surface targeting and subsequent internalisation and can also elicit a functional effect upon internalisation. This review examines various cancer targeting cell-internalising aptamers, with a particular focus towards functional aptamers that do not require additional conjugation to nanoparticles or small molecules to elicit a biological response. With a deeper understanding and precise exploitation of cancer specific molecular pathways, functional intracellular DNA aptamers may be a powerful step towards more widespread development of precision therapeutics.